Servant leadership an action: how you can achieve great relationship and results - Gazizova, S.; Prmagambetova, D. (KAZGUU Liberal Arts Digest Volume 3. M. NARIKBAYEV KAZGUU UNIVERSITY SCHOOL OF LIBERAL ARTS, 2022)
Every aspect of our society has been harmed by leaders who are only looking out for themselves, and we have all witnessed this. They frequently wind up being responsible for the downfall of their entire corporation. However, there is yet another approach, and that is servant leadership. Leaders who are servants to their followers gain power not by elevating themselves but by serving those they lead. This compilation features the contributions of forty-four renowned servant leadership experts and practitioners. These contributors include prominent business executives, bestselling authors, and respected spiritual leaders. They offer advice and tools for implementing this proven, but for some still radical, leadership model. This is the most comprehensive and all-encompassing guide that has ever been published for what is, in every respect, a superior way to lead. It was edited by Ken Blanchard, a renowned business author who has been a servant leader his entire life, and Renee Broadwell, who has been his editor for many years
Keywords: business, leadership, relationship, results, servant leadership